Anxiogenic effect of naltrexone in social interaction test in rats - Zhang Han-Xia; Xu Zhi-Ming; Luo Zhi-Pu; Qin Bo-Yi (Acta Pharmacologica Sinica; Vol 17, No 4 (July 1996): Acta Pharmacologica Sinica, 2016)
AIM: To study the anxiogenic effect of naltrexone (Nal) on the emotional state of rats. METHODS: The duration of active interaction was measured in the social interaction test in rats. RESULTS: Without influence on the locomotor activity, Nal (0.1-50 mg.kg-1) dose- and time-dependently decreased the duration of active interaction, which was antagonized by morphine (5 mg.kg-1) or fenclonine (Fen, 150 mg.kg-1 x 3 d) and was enhanced by 5-hydroxytryptophan (5-HTP, 50 mg.kg-1). CONCLUSIONS: Nal produced anxiety via its blockade of opioid receptors; central opioidergic neurons were involved in the regulation of anxiety through their tonic inhibitions in serotonergic neurons.